Lateral particle migration in shear-thinning colloidal dispersion - Kim, Young Hwan; Shim, Tae Soup; Kim, Ju Min (Korea Australia Rheology Journal, 2022)
Colloidal dispersions have been frequently encountered in a wide range of industrial applications, such as foods, paints, and Li-ion electrode slurries. Therefore, it is essential to understand the rheological and flow characteristics of colloidal dispersions to improve the quality and optimize the processing conditions of colloidal products. The shear viscosity of a colloidal dispersion deviates from Newtonian behavior, exhibiting shear thinning and/or shear thickening as the volume fraction of the colloidal particles increases. However, there are not many reports on the non-Newtonian flow phenomena caused by the normal stress differences of colloidal dispersion due to their small magnitude. Recently, these normal stress differences in colloidal dispersions with a constant shear viscosity lead to a single-line focused streams of micron-sized particles along the centerline of microchannels. In this study, the lateral migration of single micron-sized particles suspended in poly (N-isopropylacrylamide) microgel dispersions with a shear-thinning viscosity was investigated. The micron-sized particles migrated toward the centerline or between the centerline and wall of a microchannel depending on the volume fraction of the colloidal particles and the flow conditions. The current findings are expected to contribute to our understanding of the non-Newtonian fluid dynamics in colloidal dispersions and flow-induced particle segregation phenomenon.
Keywords: Colloidal dispersion; Lateral particle migration; Microchannel; Shear-thinning